When Do Scanograms and Standing Ankle Radiographs Differ? A Comparative Analysis of Ankle Alignment Measurements - In Uk Yeo; Tae Gyun Kim; Byung Ki Cho; Young Ki Min; Hyung Gyu Cho; Chang-Geun Yu; Jae Hwang Song (Journal of Clinical Medicine, 2026)
Background: Lower extremity scanograms are widely used to evaluate lower limb alignment and are frequently used as a substitute for standing ankle radiographs in retrospective studies. However, their reliability for evaluating ankle osteoarthritis remains unclear. This study investigated radiographic discrepancies between lower extremity scanograms and standing ankle radiographs and identified the patient populations in whom scanograms may not be an appropriate alternative. Methods: This retrospective study included 90 ankles that underwent both lower extremity scanograms and standing ankle radiographs. Based on the agreement of Takakura staging between the two imaging modalities, ankles were classified into a non-discrepancy group (NDG), discrepancy group (DG), or inadequate visualization group (IVG). Radiographic parameters were compared between groups and between imaging modalities. Results: Patients in the IVG had significantly lower Takakura stages than those in the NDG + DG group on standing ankle radiographs (p = 0.013), suggesting that inadequate visualization was more frequently associated with early-stage ankle osteoarthritis. Talar tilt angle (TT) measured on scanograms (p = 0.008) and tibial anterior surface angle (TAS) measured on both scanograms (p = 0.013) and standing ankle radiographs (p = 0.005) also differed significantly between the groups. Compared with the DG, the NDG demonstrated significantly higher Takakura stages on scanograms (p = 0.012). Within-patient comparisons revealed statistically significant differences in TT, TAS, and tibial plafond inclination (TPI) between the two imaging modalities; however, the clinical relevance of these differences remains uncertain because validated thresholds for clinically meaningful differences between the two imaging techniques have not been established. Staging discrepancies were significantly more common in early-stage (Takakura stages 1–3a) than advanced-stage (stages 3b–4) ankle osteoarthritis (p = 0.010). Conclusions: In this retrospective, single-center study of 90 ankles, lower extremity scanograms showed discrepancies from standing ankle radiographs in the evaluation of ankle osteoarthritis, particularly in early-stage disease. These findings suggest that scanograms may not provide equivalent ankle-specific information in all patients. Standing ankle radiographs may be considered when precise ankle-specific assessment is clinically important, particularly in patients with suspected early-stage ankle osteoarthritis.